The Internal, External and Extended Microbiomes of Hominins - Dunn, Robert R.; Amato, Katherine R.; Archie, Elizabeth A.; Arandjelovic, Mimi; Crittenden, Alyssa N.; Nichols, Lauren M. (Frontiers in Ecology and Evolution, 2020)
The social structure of primates has recently been shown to influence the composition of their microbiomes. What is less clear is how the microbiome composition of primates might influence their social behavior, either in general or with particular reference to hominins. Here we use a comparative approach to understand how microbiomes of hominins have, or might have, changed since the last common ancestor of chimpanzees and humans, roughly six million years ago. We focus on microbiomes associated with social evolution, namely those hosted or influenced by stomachs, intestines, armpits, and food fermentation. In doing so, we highlight the potential influence of microbiomes in hominin evolution while also offering a series of hypotheses and questions with regard to evolution of human stomach acidity, the factors structuring gut microbiomes, the functional consequences of changes in armpit ecology, and whether Homo erectus was engaged in fermentation. We conclude by briefly considering the possibility that hominin social behavior was influenced by prosocial microbes whose fitness was favored by social interactions among individual hominins.